The Role of Political Communication in Shaping Public Perception of Godfatherism and Godson Conflicts in the Nigerian Political Sphere - Gana, Stephen; Inobemhe, Kelvin; Udeh, Nick-Tansi (ENCOMMUNICATION: Journal of Communication Studies, 2025)
This study examines the influence of political communication strategies on public perception and understanding of godfatherism and godson conflicts in Nigeria. The primary objective is to analyze how media framing, social media, and political rhetoric shape public attitudes towards these political dynamics. The study is grounded in the framing and agenda-setting theories, which explores how media and communication strategies influence and shape public interpretation of political issues through framing and constant focus on such issues. A mixed-methods approach was employed, combining qualitative content analysis of media reports and interviews with political analysts, alongside a quantitative survey of public opinions. Findings reveal that traditional media, particularly news outlets aligned with political figures, frame godfatherism as either a stabilizing force or a corrupt practice, significantly influencing public opinion. Social media platforms also contribute to the spread of misinformation, intensifying partisan divides. Politicians' strategic use of campaign messages further polarizes views, with some presenting godfatherism as beneficial while others critique it as detrimental to democracy. The study concludes that political communication plays a pivotal role in shaping public understanding of godfatherism, either fostering informed engagement or reinforcing apathy. It recommends promoting media literacy, encouraging independent journalism, and fostering a more transparent political discourse to reduce the negative effects of biased political narratives.